Reports on hospitals and the patient and a domestic workers' charter - Great Britain. Standing Joint Committee of Industrial Women's Organisations ; Labour Party (Great Britain). Advisory Committee on Public Health (London : Labour Party, 1931)
1931 1931 1930s 22 pages material matching the bed curtains, or plain to match the walls. Furniture. Every ward should have a wardrobe for the clothes of those people who have come a distance and who have no one to take them away. This can be put outside the ward, or even in another part of the hospital. One of the most interesting pieces of ward furniture to the patient is the wheeled chair, which is used when first allowed up. This usually has adjustable leg rests, but rarely has an adjustable back, or a place for a tumbler. All ordinary chairs in use in a ward should be fitted with domes of silence. A few low stools would be of great use in a ward to assist patients to get back into high beds. Lights. Apart from the usual overhead lighting every patient needs a light behind the bed, preferably at the side. This must fit in a socket, so that it can be taken down for use on the bed for night dressings, and night lamps should have green covers in place of the usual red ones. B. WAKING HOUR Sleep. Sick persons need much sleep and generally speaking, the more sleep they can get the better for them. Patients who are nursed at home or who have a room to themselves, usually drop off for a short sleep several times during the day, but in a hospital ward, where there is something going on almost the whole day, this is more difficult. Besides this, watching the general activities of the ward, which patients generally find on the whole interesting, and which makes a spell of sickness spent in a hospital ward much less boring than one in a single room, is, at the same time, apt to be fatiguing, so that a longer time of undisturbed quiet is necessary at night. Present Practice. In most hospitals patients are awakened early. In a good many they are washed at 5 a.m.; in a few, even before this hour. There are very few hospitals in England in which the patients are allowed to sleep after 6 a.m. The reason for this practice is to be found in the fact that the hospitals of Britain have been evolved as (9) 126/TG/RES/X/1036A/7